A covenant of creatures: Levinas's philosophy of Judaism - Fagenblat, Michael (Cultural memory in the present, 2010)
Levinas's new creation : a philosophy of Judaism, without and or between -- From chaos to creation : the genesis of ethics -- Ethics in the image of God : anthropology ex nihilo -- Interlude : from moral creators to ethical creatures : Levinas's kehre -- Ethical negative theology -- Secularizing the covenant : the ethics of faith -- The ambivalence of fraternity : ethical political theology